Counseling Practicum Students’ Experiences Working with Children with Learning Exceptionalities - Kathryn Babb; Viki Kelchner; Laurie O Campbell (Teaching and Supervision in Counseling, 2023)
School-based practicums provide opportunities for counselors-in-training to provide supervised counseling services to youth while providing authentic, immersive counseling experiences for the counselor. Children counseled may identify with or without exceptionalities. The researchers sought to understand the experiences of five counselors-in-training who counseled children with exceptionalities during a semester-long school-based practicum. In this phenomenological study, researchers thematically coded transcripts from a focus group about counseling children with exceptionalities. Three themes were identified: (a) counselors-in-training identity inclusive of anticipated counselor identity versus their practical identity, (b) acceptance inclusive of acceptance of self and acceptance of clients, and (c) worldview inclusive of culture shaping, personal experiences, and biases. The findings are relevant to counselor educators, counselors-in-training, and exceptional education departments.
Keywords: counselors-in-training; exceptionalities; counselor identity; acceptance; worldview.